Obesity and low levels of physical activity impact on cardiopulmonary fitness in older men after treatment for prostate cancer. (18th June 2021) - Faithfull, Sara; Lemanska, Agnieszka; Poole, Karen; Aning, Jonathan; Manders, Ralph; Marshall, John; Saxton, John; Turner, Lauren; Griffin, Bruce
Abstract: The purpose of this study was to compare fitness parameters and cardiovascular disease risk of older and younger men with prostate cancer (PCa) and explore how men's fitness scores compared to normative age values. 83 men were recruited post‐treatment and undertook a cardiopulmonary exercise test (CPET), sit‐to‐stand, step‐and‐grip strength tests and provided blood samples for serum lipids and HbA1c. We calculated waist‐to‐hip ratio, cardiovascular risk (QRISK2), Charlson comorbidity index (CCI) and Godin leisure‐time exercise questionnaire [GLTEQ]. Age‐group comparisons were made using normative data. Men > 75 years, had lower cardiopulmonary fitness, as measured by VO2 Peak (ml/kg/min) 15.8 + 3.8 p < 0.001, and lower grip strength(28.6+ 5.2 kg p < 0.001) than younger men. BMI ≥30kg/m 2 and higher blood pressure all contributed to a QRisk2 score indicative of 20% chance of cardiovascular risk within 10 years (mean: 36.9–6.1) p < 0.001. Age, BMI and perceived physical activity were significantly associated with lower cardiopulmonary fitness. Men with PCa > 75 years had more cardiovascular risk factors compared to normative standards for men of their age. Although ADT was more frequent in older men, this was not found to be associated with cardiopulmonary fitness, but obesity and low levels of physical activity were. Secondary prevention should be addressed in men with PCa to improve men's overall health.